2004
DOI: 10.1111/j.1440-1827.2004.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes tumor of the seminal vesicle: Case report and literature review

Abstract: A 39-year-old man presented with urinary retention and lower abdominal discomfort at our hospital, and a computed tomography scan showed a huge cystic mass posterior to the urinary bladder. During surgical exploration, a mass superior to the prostate in the region of the left seminal vesicle was found. Histologically, the tumor was characterized by cystically dilated or slit-like glands mixed in a densely cellular stroma with pleomorphism and resembled those of phyllodes tumor of the breast or prostate. The gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The focal necrosis was < 5% of the total mass and other histological features were compatible with low-grade phyllodes tumour: the tumour had an intact external surface with no infiltrating margins and macroscopically the mass had a cystic nature, whereas high-grade phyllodes tumours are usually solid. 8 In addition, the outcome was consistent with a histological classification between low and high grade.…”
Section: Discussionsupporting
confidence: 73%
“…The focal necrosis was < 5% of the total mass and other histological features were compatible with low-grade phyllodes tumour: the tumour had an intact external surface with no infiltrating margins and macroscopically the mass had a cystic nature, whereas high-grade phyllodes tumours are usually solid. 8 In addition, the outcome was consistent with a histological classification between low and high grade.…”
Section: Discussionsupporting
confidence: 73%
“…18 He also highlighted the histologic and ultrastructural differences based on simpler gland configuration, different acinar epithelium, and the fewer electron-lucent secretory granules seen in mammary glands. 1 Additional support for the theory for mammary-like anogenital glands being the origin of mammary-type neoplasms and conditions, including phyllodes, comes from reports of those entities in regions that are not part of the caudal milk line, including phyllodes of the perianal region, 3,13 prostate, 18,19 and seminal vesicle. 19,20 Giger et al 20 demonstrated strong NY-BR-1 expression by the phyllodes tumor of the vulva with similar strong expression from nearby mammary-like anogenital glands, suggesting that the phyllodes tumor of the vulva likely originate from these glands.…”
Section: Pathogenesismentioning
confidence: 99%
“…1 Additional support for the theory for mammary-like anogenital glands being the origin of mammary-type neoplasms and conditions, including phyllodes, comes from reports of those entities in regions that are not part of the caudal milk line, including phyllodes of the perianal region, 3,13 prostate, 18,19 and seminal vesicle. 19,20 Giger et al 20 demonstrated strong NY-BR-1 expression by the phyllodes tumor of the vulva with similar strong expression from nearby mammary-like anogenital glands, suggesting that the phyllodes tumor of the vulva likely originate from these glands. The involvement of hormones in the development of phyllodes tumors of the vulva is suggested by reports that correlate the appearance of tumor with the onset of puberty 14 and rapid growth during 17-b-estradiole treatment for menopausal symptoms.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Extra-mammary phyllodes tumors have been reported in the prostate and seminal vesicles [1,2]. Mesenchymal tumors involving the pancreas are rare, but various histological types have been reported, including leiomyosarcoma, leiomyoma, inflammatory myofibroblastic tumor (IMT), perivascular epithelioid cell tumor, schwannoma, solitary fibrous tumor (SFT), and extra-gastrointestinal stromal tumor (extra-GIST) [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%